The Incidence, Distribution and Clinicopathology of Missed Colorectal Cancer After Diagnostic Colonoscopy - Laurent, Edward; Hussain, Hadi; Calvin Poon, Tak Kit; Ayantunde, Abraham A. (Turkish Journal of Gastroenterology, 2021)
Background: Colonoscopy does miss some lesions that may be later diagnosed as post-colonoscopy colorectal cancers (PCCRCs). We evaluated the rate of PCCRCs in a cohort of our patients. Methods: The data of patients diagnosed with first primary colorectal cancers (CRCs) between July 2014 and June 2017 were analyzed. Colorectal cancers were considered to be missed if they occurred among patients who have had an index colonoscopy between 7 and 36 months prior to their diagnosis. The incidence of missed lesions and the distribution of such lesions in the large bowel are presented. Results: In the study, 399 of the total 541 patients whose CRCs were diagnosed by colonoscopy were included. The median age of the patients (213 males and 186 females) was 75.3 (32.4-82.1) years. Seven patients with diagnosis of primary CRCs had undergone index colonoscopy between 7 and 36 months prior to their diagnostic colonoscopy. Therefore, the PCCRC rate in this cohort was 1.8% (7/399 × 100). The mean time interval between the false negative colonoscopy (index colonoscopy) and diagnostic colonoscopy was 18.7 (9.1- 34.9) months. Missed CRCs were located in the ascending (2), transverse (1), descending (1), and sigmoid colon (2) and in the rectum (1). Conclusion: Our PCCRC rate was 1.8%, which is lower than the usually reported rate